A Dual Eye Tracking Study of Joint Attention in Adults with Autism Spectrum Disorder. - MANÇE ÇALIŞIR, Öykü; ÇAKIR, Murat Perit; ACARTÜRK, Cengiz; ATBAŞOĞLU, Eşref Cem (Archives of Neuropsychiatry / Nöropsikiyatri Arşivi, 2025)
Introduction: Joint attention ( JA) is a fundamental aspect of social interaction and a cornerstone of social communication. This study explores factors influencing JA in adults with Autism Spectrum Disorder (ASD) using an interactive, dual eye-tracking paradigm during a tangram puzzle computer gameplay. The JA performance of adults with ASD and a typically developing non-clinical control group (TD-NCC) was assessed alongside partner familiarity (familiar / stranger), partner roles (presenter / operator) and gaze cue (present / absent). Two main objectives were: 1) to evaluate JA through gaze recurrence (GR) in adults with ASD, and 2) to examine the effect of partner familiarity on JA by comparing the performance in the task conducted with either a familiar or an unfamiliar partner (stranger). Methods: The sample consisted of 42 participants (21 adults with ASD; ages 18--50, 9 females and 12 males and 21 TD-NCC; ages 21--50, 11 females and 10 males). Two non-intrusive desktop eye trackers simultaneously recorded gaze during the JA tangram task. Gaze recurrence was used as an indicator of JA. The gaze cue (present/absent) was a semi-transparent indicator showing where to look. Additionally, to control for potential eye pathophysiology in JA, saccade and antisaccade tasks were applied to the eye movements of each participant. Results: The Linear Mixed Effect Model revealed that GR was significantly lower in the ASD group compared to controls. However, the presence of a gaze cue significantly improved the ASD group's GR, especially when interacting with a familiar partner under gaze-cue on conditions. Conclusion: Understanding factors influencing JA in autism may foster further exploratory studies and significantly impact future research. Eye movements may serve as objective, quantitative, and non-invasive biomarkers for ASD, particularly in interactive gaming contexts.